Construction and Analysis of an Adapted Spectral Finite Element Method to Convective Acoustic Equations (Communications in Computational Physics, 2018)
The paper addresses the construction of a non spurious mixed spectral finiteelement (FE) method to problems in the field of computational aeroacoustics. Basedon a computational scheme for the conservation equations of linear acoustics, the extensiontowards convected wave propagation is investigated. In aeroacoustic applications,the mean flow effects can have a significant impact on the generated soundfield even for smaller Mach numbers. For those convective terms, the initial spectralFE discretization leads to non-physical, spurious solutions. Therefore, a regularizationprocedure is proposed and qualitatively investigated by means of discrete eigenvaluesanalysis of the discrete operator in space. A study of convergence and an applicationof the proposed scheme to simulate the flow induced sound generation in the processof human phonation underlines stability and validity.